Immunometabolic programming of macrophages in asthma pathogenesis and therapy - Lu, Lisha; Shi, Mengdi; Qin, Wen; Yang, Mingshu; Wang, Xiaochang; Wang, Youpeng (Frontiers in Physiology, 2026)
Asthma is a heterogeneous chronic airway disease in which immune dysregulation and metabolic imbalance jointly shape inflammatory phenotypes and clinical outcomes. Growing evidence identifies pulmonary macrophages as central integrators of inflammatory cues and metabolic programs, linking acute exacerbations with long-term airway remodeling. Distinct tissue-resident and monocyte-derived macrophage subsets polarize along an M1–M2 spectrum and adopt glycolysis-dominated pro-inflammatory states or fatty acid oxidation-centered reparative states that differentially drive neutrophilic versus type 2-biased eosinophilic inflammation. Rewiring of arachidonic acid–derived eicosanoid synthesis and cholesterol handling further tailors macrophage effector functions and modulates responsiveness to glucocorticoids. Preclinical studies demonstrate that pharmacological manipulation of macrophage glucose and lipid metabolism can attenuate airway hyperresponsiveness and structural remodeling, highlighting immunometabolic circuits as promising therapeutic targets in asthma. This review summarizes current advances in macrophage ontogeny, polarization and metabolic reprogramming in the asthmatic lung. It also discusses how these insights may inform metabolism-focused, macrophage-directed interventions.